The role of prehabilitation on short‐term outcomes after liver transplantation: A review of the literature and expert panel recommendations. Issue 10 (9th December 2022) - Vinaixa, Carmen; Martínez Palli, Graciela; Miliken, Donald; Sellers, Daniel; Dharancy, Sebastien; Spiro, Michael; Aristotle Raptis, Dimitri; Samuel, Didier; ,
Abstract: Background: Prehabilitation programs as part of ERAS protocols are being increasingly used in multiple surgeries, improving postoperative outcomes. Data regarding prehabilitation programs in patients awaiting liver transplantation and their outcomes is scarce. Objectives: To identify whether prehabilitation programs based on exercise training conducted prior to liver transplantation improve short‐term postoperative outcomes, and to provide expert panel recommendations. Data sources: Ovid MEDLINE, Embase, Scopus, Google Scholar, and Cochrane Central. Methods: Systematic review following PRISMA guidelines and recommendations using the GRADE approach derived from an international expert panel. Studies included those evaluating postoperative outcomes, as well as those evaluating functional outcomes. PROSPERO ID: CRD42021236305. Results: Of the 170 studies screened, only one assessed the primary objective. Most studies focus on the preoperative impact of exercise training on aerobic capacity, muscle mass and/or strength, showing positive effects and no significant adverse events, but are underpowered and with heterogenous designs and interventions. The non‐randomized observational study which assessed relevant postoperative outcomes, showed a non‐significant trend towards reduced 90‐day readmission rate and shorter length of stay in the prehabilitation group. Conclusions: Prehabilitation prior to liver transplantation is unlikely to be harmful, and likely to have short term benefits on functional status. We cautiously recommend prehabilitation on the basis of absence of harm and possibility of benefit ( Quality of Evidence; Very Low | Grade of Recommendation; Low ).